2001
DOI: 10.1093/treephys/21.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic control of seasonal development and dormancy in tropical stem-succulent trees

Abstract: Tropical stem-succulent trees store large quantities of water in their trunks yet remain leafless during the early and mid dry season. In contrast to most other tropical trees, bud break of vegetative buds is not induced in fully hydrated stem succulents between the winter solstice and the spring equinox by leaf abscission, abnormal rain showers or irrigation. Vegetative buds of leafless trees are therefore in a state of endo-dormancy similar to that of temperate perennial plants during early winter. Highly sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
3
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 16 publications
14
135
3
8
Order By: Relevance
“…This rainfall is unlikely to influence soil water availability for the trees, but may facilitate leaf flushing by increasing relative humidity and reducing vapour pressure deficit Myers et al 1998). Water storage within plants may also influence phenological patterns (Borchert 1994a;Borchert and Rivera 2001;Rivera et al 2002;Chapotin et al 2006). In this study, however, water storage ability was not observed to facilitate dry season leaf flushing, with the two stem succulent species (Spondias pinnata and Tetrameles nudiflora) observed to consistently flush leaves during the early wet season.…”
Section: Timing and Patterns Of Leaf Flushingcontrasting
confidence: 53%
“…This rainfall is unlikely to influence soil water availability for the trees, but may facilitate leaf flushing by increasing relative humidity and reducing vapour pressure deficit Myers et al 1998). Water storage within plants may also influence phenological patterns (Borchert 1994a;Borchert and Rivera 2001;Rivera et al 2002;Chapotin et al 2006). In this study, however, water storage ability was not observed to facilitate dry season leaf flushing, with the two stem succulent species (Spondias pinnata and Tetrameles nudiflora) observed to consistently flush leaves during the early wet season.…”
Section: Timing and Patterns Of Leaf Flushingcontrasting
confidence: 53%
“…The long-term observation of many forest species in Costa Rica (ca. 10º N) indicates that leaf fall and bud emergence take place during the driest and warmest part of the year, coinciding with the spring equinox (Borchert, 1994a;Borchert and Rivera, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that DL alone is the cue to phenology has been defended several times (e.g. Borchert et al, 2005;Borchert and Rivera, 2001) but more recently Calle et al (2009) suggested that insolation near the autumn equinox, not DL, is the driver of flower phenology. Usually, it is not possible to separate the effect on leaf abscission of water deficit or DL under natural conditions, because abscission intensifies when water deficit increases and DL declines (Borchert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Borchert & Rivera (2001) em estudo com espécies arbóreas de caules suculentos verificaram que essas plantas permaneciam inativas do início para o meio da estação seca, até mesmo quando eram irrigadas. Concluíram que a disponibilidade de água não estava determinando a ocorrência do brotamento, e que a variação sazonal no fotoperíodo era o fator que determinava a ocorrência das fenofases vegetativas e não a disponibilidade de água no solo, mesmo em baixas latitudes, onde a variação anual do comprimento do dia é inferior a uma hora, sendo a dormência induzida e quebrada por variações no fotoperíodo de menos de 30 min.…”
Section: Número De Folhas (Nf)unclassified